What Is New in the Anti–Pseudomonas aeruginosa Clinical Development Pipeline Since the 2017 WHO Alert? - Reig, Sébastien; Le Gouellec, Audrey; Bleves, Sophie (Frontiers in Cellular and Infection Microbiology, 2022)
The spread of antibiotic-resistant bacteria poses a substantial threat to morbidity and mortality worldwide. Carbapenem-resistant Pseudomonas aeruginosa (CRPA) are considered “critical-priority” bacteria by the World Health Organization (WHO) since 2017 taking into account criteria such as patient mortality, global burden disease and worldwide trend of multi-drug resistance (MDR). Indeed P. aeruginosa can be particularly difficult to eliminate from patients due to its combinatory antibiotic resistance, multifactorial virulence and ability to over-adapt in a dynamic way. Research is active but the course to a validated efficacy of a new treatment is still long and uncertain. What’s new in the anti-P. aeruginosa clinical development pipeline since the 2017 WHO alert? This review focuses on new solutions for P. aeruginosa infections that are in active clinical development, i.e., currently being tested in humans and may be approved for patients in the coming years. Among 18 drugs of interest in December 2021 anti-P. aeruginosa development pipeline described here, only one new combination of β-lactam/β-lactamase inhibitor is in phase III trial. Derivatives of existing antibiotics considered as “traditional agents” are over-represented. Diverse “non-traditional agents” including bacteriophages, iron mimetic/chelator and anti-virulence factors are significantly represented but unfortunately still in early clinical stages. Despite decade of efforts, there is no vaccine currently in clinical development to prevent P. aeruginosa infections. Studying pipeline anti-P. aeruginosa since 2017 up to now, shows how to provide a new treatment for patients can be a difficult task. Given the process duration, the clinical pipeline remains unsatisfactory leading best case to the approval of new antibacterial drugs that treat CRPA in several years. Beyond investment needed to build a robust pipeline, the Community needs to reinvent medicine with new strategies of development to avoid the disaster. Among “non-traditional agents”, anti-virulence strategy may have the potential through novel and non-killing modes of action to reduce the selective pressure responsible of MDR.